Mini cakes prepared with press-cake flour obtained from the oil extraction from araticum seeds (Annona crassiflora mart.) - BRAGA, Lucas Pereira; AMORIM, Katiúcia Alves; GOULART, Gilberto Alessandre Soares; ASQUIERI, Eduardo Ramirez; DAMIANI, Clarissa (Food Science and Technology, 2024)
This study aimed to reuse the residue of oil extraction from araticum seeds (AS) (press-cake) applied in mini-cake formulation, partially replacing wheat flour. AS and formulations with different proportions of press-cake flour from araticum seeds (PCFAS) were investigated. The proportions were 0, 5, 10, 15, and 20% of PCFAS in partial replacement of wheat flour. AS, PCFAS, and mini cakes were evaluated for chemical composition, total phenolics, and antioxidant capacity using the FRAP, DPPH, and ABTS methods. The partial wheat flour substitution effects were evaluated by texture, shear, and color parameters. The PCFAS incorporation significantly influenced the mini cakes, providing greater firmness, shear strength, browning of the core, and increased antioxidant capacity. According to the results, AS and PCFAS have high antioxidant capacity and phenolic concentration. The mini cake with 20% PCFAS was considered the best formulation due to an increase in protein, lipid, and antioxidant capacity.